Whitlam's Children : Labor and the Greens in Australia - Crowe, Shaun; Gallop, Geoff (Victoria : Melbourne University Publishing, 2018)
"Over the past three decades, progressive politics in Australia has undergone a gradual but unmistakable transformation. Where the Australian Labor Party once enjoyed dominance over the political left it now shares space with the Greens; at times depending on minor-party support to form government, and even more often to pass contentious legislation. Based on over forty interviews with politicians and party figures, Whitlam's Children is the first study of this increasingly important relationship in Australian politics. Did previous attempts at cooperation, particularly minority government under Julia Gillard, deliver successful government, and how do each judge the experiment in hindsight? Why are certain policy areas, like refugee settlement and environmental policy, so stubborn and divisive? And will we ever see a more lasting coalition on the Australian left, to mirror the established arrangement on the Australian right? While revealing a variety of perspectives, even within parties, the research uncovers a productive..."--Publisher's summary.
Intro; Title; Copyright; Contents; Foreword by Geoff Gallop; Acknowledgements; Introduction; 1 The Two-party System and its Discontents; 2 Two Leftist Traditions: What divides Labor and the Greens?; 3 The View from the Top: Why Labor or the Greens?; 4 Beautifully Ugly? Labor, the Greens and minority government; 5 The Diabolical Problem; 6 Refugee Politics; 7 Taxing Mining; 8 A 'Red-Green' Coalition?; Conclusion: 'Certainly, the impotent are pure'; References; Index.
Includes bibliographical references and index.
eBook access via Internet.
Online resource; title from EPUB title page (OverDrive, viewed October 2, 2018)
Keywords: Australian Greens; Australian Labor Party; Green Party (Australia); Green Party (Australia); Intra-party disagreements (Political parties); Labor movement -- Australia; Labor movement -- History; Political leadership -- Australia; Political parties -- Australia -- History; Political parties -- Australia; Politicians -- Australia -- Interviews; Political parties; POLITICAL SCIENCE / World / Australian & Oceanian; Australia -- Politics and government -- 21st century; Australia; Australian; Electronic books; Electronic books